Harvesting New Chiral Phosphotriesters by Phosphorylation of BINOL and Parent Bis-phenols - Ndimba, A. Ngo; Roisnel, T.; Argouarch, G.; Lalli, C. (Synthesis, 2019)
A systematic study on the phosphorylation of BINOL and other bis-phenols with chlorophosphates is described. An intriguing reactivity has been observed that is attributable to the hydroxyl group acidity and to the leaving group nucleofuge character within the phosphorylating agent used. By playing on these two parameters, new chiral monophosphotriesters, symmetrical homo-BINOL bisphosphates, and unsymmetrical non-homo-BINOL derivatives incorporating a non-chiral side unit, were synthesized selectively and in good yields.
Keywords: chiral phosphotriesters; chiral phosphates; BINOL; bis-phenols; phosphorylation